LITERATURE REVIEW THE EFFECT OF MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PRODUCTIVITY & PERFORMANCE - Ronaldy Irfak (Dinasti International Journal of Education Management And Social Science, 2022)
The purpose of this study is to reveal the effect of the Papuan Orang Asli (OAP) application on human resources in Sarmi district where through this application the government will be able to find out the total number of OAP domiciled in Sarmi district and can see the level of welfare of the Papuan people themselves through the type of work. them, so that later government assistance such as village budget, social housing assistance, direct cash assistance, BPJS Social assistance, etc., will really be right on target. In addition, through this application, it is hoped that later when the selection or appointment of civil servants specifically for native Papuans can be used as a comparison material, how many percent must be accepted or appointed as prospective civil servants in Sarmi Regency.